2012
DOI: 10.1002/jts.21732
|View full text |Cite
|
Sign up to set email alerts
|

Modeling PTSD Symptom Clusters, Alcohol Misuse, Anger, and Depression as They Relate to Aggression and Suicidality in Returning U.S. Veterans

Abstract: Suicidal ideation (SI) and aggression are common correlates of Posttraumatic Stress Disorder (PTSD) among Iraq and Afghanistan War veterans. The existing literature has established a strong link between these factors, but a more nuanced understanding of how PTSD influences them is needed. The current study examined the direct and indirect relationships between PTSD symptom clusters and SI and general aggression (without a specified target) via depression, alcohol misuse, and trait anger. Participants were 359 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
111
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 56 publications
19
111
5
Order By: Relevance
“…The findings suggested positive correlations between each of the three PTSD symptom clusters and violent behaviors. This finding extended the results of previous studies (Barrett et al 2011;Hellmuth et al 2012;Taft et al 2007a), and also supported the Holtzworth-Munroe (1992) model. Results also showed that only the avoidance symptom clusters of PTSD was positively related to suicidal ideation, which also corroborated previous studies (Davis et al 2014;Guerra and Calhoun 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings suggested positive correlations between each of the three PTSD symptom clusters and violent behaviors. This finding extended the results of previous studies (Barrett et al 2011;Hellmuth et al 2012;Taft et al 2007a), and also supported the Holtzworth-Munroe (1992) model. Results also showed that only the avoidance symptom clusters of PTSD was positively related to suicidal ideation, which also corroborated previous studies (Davis et al 2014;Guerra and Calhoun 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Possible differential effects of PTSD and venting negative feelings on these two types of aggression have not been investigated. Thus, exploring the relationship of PTSD and venting negative feelings with violent behaviors and suicidal ideation is an integral step towards a better understanding of the different components of PTSD (Hellmuth et al 2012). In exploring this relationship, we can also examine how specific symptoms of PTSD are related to violent behaviors and suicidal ideation under different degrees of venting negative feelings.…”
mentioning
confidence: 99%
“…These findings also take on additional clinical importance as suicidality and aggression have been shown to share many of the same risk factors in studies of veterans (Hellmuth et al, 2012). Given prior work demonstrating that genetic factors account for much of the shared variance in the internalizing and externalizing dimensions of psychopathology (Kendler et al, 2003), the present findings suggest the possibility that the relationship between violence toward self and others may be due in part to shared genetic variance with the distress factor of psychopathology; however, additional research is needed to explicitly test this hypothesis.…”
Section: Discussionmentioning
confidence: 85%
“…Further, veterans of these conflicts have high rates of PTSD (Hoge et al, 2004), and PTSD has been found to be robustly associated with anger (Calhoun et al, 2002;Crawford, Calhoun, Braxton, & Beckham, 2007), intimate partner violenceSome researchers have suggested that examining the specific symptom profiles within PTSD may yield information regarding violence risk. Specifically, hyper-arousal symptoms of PTSD have often been found to be more predictive of aggression than avoidance or reexperiencing symptoms (Barrett, Mills, & Teesson, 2011;Macmanus et al, 2013;McFall et al, 1999;, although the findings in this regard have been mixed and are often not straightforward (Hellmuth, Stappenbeck, Hoerster, & Jakupcak, 2012;Savarese, Suvak, King, & King, 2001). …”
Section: Introductionmentioning
confidence: 99%